The Relationship between Physical Activity with Increased Learning Concentration Among Students at Senior High School 3 Denpasar - I Putu Yudi Pramana Putra; M. Widnyana; I Dewa Gede Alit Kamayoga; Ni Luh Putu Gita Karunia Saraswati; Anak Agung Gede Eka (Physical Therapy Journal of Indonesia, 2021)
Introduction: Physical activity is any body movement caused by the work of skeletal muscles system and increases the expenditure of effort and energy. The energy is used as fuel to perform motion and function. Nutrition and oxygen throughout the tissue will be better with increased physical condition which showed by increased in the amount of hemoglobin in the blood. Increased concentration will occur when the two energy substances in the human brain effect and fastering body's circular system. Objective: To determine the relationship between physical activity with increasing concentration on students in learning at senior high school 3 Denpasar. Methods: The sampling technique in this study was consecutive sampling. This study used an observational method with a cross sectional design. This research collects data from 122 students at senior high school 3 Denpasar which will measure the level of physical activity and concentration. Results: The results showed that there was a significant relationship between physical activity with increase in learning concentration on students at senior high school 3 Denpasar (r=0,737; p<0,05). Conclusion: There is a significant relationship with a positive value between physical activity with an increase in learning concentration on students at senior high school 3 Denpasar. If physical activity increases, the concentration of learning will also increase